2023
DOI: 10.3390/idr15010005
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bacteriuria in Patients with Type 2 Diabetes Mellitus

Abstract: Objectives: Asymptomatic bacteriuria (ASB) is a common finding in patients with diabetes. Moreover, patients with diabetes and ASB have a greater risk for symptomatic urinary tract infections and associated severe complications. The aim of this study was to estimate the prevalence of ASB, as well as to identify independent risk factors and related pathogens associated with ASB in female and male patients with type 2 diabetes mellitus (T2D). Methods: This prospective case-control study was performed at the Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The mean age (54.5 AE 11.4 years) of the participants was comparable to the mean age of the participants in the study by Banerjee et al, probably because of similar sociodemographic factors and study design. 25 However, it was lower than that of the participants in the studies by Asghar et al, 26 Odetoyin et al, 10 and Matthiopoulou et al, 6 and higher than that of the participants in the studies by Venketesen et al 7 and Bissong et al 12 These differences may be results of differences in sample size, study location, or the age group of the participants.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The mean age (54.5 AE 11.4 years) of the participants was comparable to the mean age of the participants in the study by Banerjee et al, probably because of similar sociodemographic factors and study design. 25 However, it was lower than that of the participants in the studies by Asghar et al, 26 Odetoyin et al, 10 and Matthiopoulou et al, 6 and higher than that of the participants in the studies by Venketesen et al 7 and Bissong et al 12 These differences may be results of differences in sample size, study location, or the age group of the participants.…”
Section: Discussionmentioning
confidence: 88%
“…4 People with T2DM are at a four-fold higher risk of ASB than those without, 4,5 and the majority of previous studies have shown that untreated ASB progresses to symptomatic urinary tract infection (UTI), which is an important cause of morbidity in patients with diabetes mellitus. [5][6][7] There is a close association between the retention of urine, owing to poor bladder function, and greater bacterial growth. 4 This rapid bacterial growth occurs in patients with T2DM in the presence of poor glycemic control, which results in poor blood supply and abnormal cell-mediated immunity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations